F-zif-67 / pdms composite film, preparation method and application thereof, and friction nanogenerator and application thereof
Patent Information
- Application Number
- CN202411447022.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-10-16
AI Technical Summary
但目前的MOFs材料作为摩擦电层还存在发电效率不高的缺陷,基于此,有必要对此进行改进
[0037]1、本发明的F-ZIF-67/PDMS复合薄膜的制备方法相对简单,通过简单的溶液混合、搅拌、固化、浸泡等步骤即可制备出高性能的F-ZIF-67/PDMS复合薄膜,这种制备方法具有成本低、操作简便、可重复性好等优点,有利于实现大规模生产和商业化应用;
Smart Images

Figure CN119331294B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of triboelectric nanogenerator technology, and in particular to an F-ZIF-67 / PDMS composite thin film, its preparation method and application, and triboelectric nanogenerator and its application. Background Technology
[0002] Metal corrosion is widespread in the construction, shipbuilding, and automotive industries, and the resulting global losses and disasters are significant. Therefore, corrosion protection has become an urgent issue. Cathodic protection, as a highly efficient corrosion prevention method, has attracted considerable attention. Traditionally, cathodic protection mainly relies on sacrificial anode cathodic protection and impressed power protection methods, but both of these methods require energy support from external equipment. Therefore, finding a reliable energy source has become a pressing problem to be solved.
[0003] Triboelectric nanogenerators (TENGs), as an emerging energy technology, can effectively convert minute amounts of mechanical energy into electrical energy, opening up new avenues for the field of metal corrosion protection. Currently, cathodic protection systems based on TENGs have been developed, but to achieve large-area cathodic protection, their output performance needs further improvement, including enhancing energy harvesting and conversion efficiency. Therefore, it is necessary to explore new methods to ensure that TENGs maintain excellent performance and stable output during operation, which is of great significance to the development of triboelectric nanogenerators and the field of corrosion protection.
[0004] In recent years, metal-organic frameworks (MOFs) have been widely used in various fields as multifunctional materials. These materials, composed of organic ligands linked to metal ions, possess high crystallinity, high specific surface area, unique morphology, tunable porosity, and high thermal and chemical stability. These properties make MOFs an ideal choice for triboelectric devices. However, current MOF materials used as triboelectric layers still suffer from low power generation efficiency, necessitating improvements. Summary of the Invention
[0005] In view of this, the present invention provides an F-ZIF-67 / PDMS composite thin film, its preparation method and application, and a triboelectric nanogenerator and its application, in order to overcome the defects of the prior art.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a method for preparing an F-ZIF-67 / PDMS composite film, comprising the following steps:
[0008] ZIF-67 powder was added to the PDMS precursor, stirred, and then ultrasonically dispersed to obtain a mixed solution; the PDMS precursor includes a curing agent and a PDMS matrix;
[0009] Vacuum the mixed solution to eliminate air bubbles in the solution;
[0010] The vacuum-sealed mixed solution was coated onto the substrate and cured to obtain a ZIF-67 / PDMS composite film.
[0011] The ZIF-67 / PDMS composite film was immersed in a fluorosilane solution and dried to obtain the F-ZIF-67 / PDMS composite film.
[0012] Preferably, the fluorosilane solution comprises perfluorodecyltrimethoxysilane and ethanol, wherein the mass concentration of perfluorodecyltrimethoxysilane in the fluorosilane solution is 1-2%.
[0013] Preferably, the method for preparing the ZIF-67 powder includes the following steps:
[0014] Co(NO3)2 was dissolved in methanol, and then a methanol solution containing 2-methylimidazole was added to obtain a mixture.
[0015] After stirring the mixture, it was aged, centrifuged, and the precipitate was obtained. The precipitate was washed and dried to obtain ZIF-67 powder.
[0016] Preferably, the ultrasonic dispersion time is 30–100 min;
[0017] And / or, the mass ratio of the curing agent to the PDMS matrix is 1:(10-12);
[0018] And / or, the mass ratio of the ZIF-67 powder to the PDMS precursor is 1:(10-100);
[0019] And / or, the curing time is 1 to 4 hours, and the curing temperature is 70 to 90°C.
[0020] Preferably, in the step of immersing the ZIF-67 / PDMS composite film in a fluorosilane solution, the immersion temperature is 20-25°C and the time is 2-3 hours;
[0021] And / or, after stirring the mixture for 2-4 hours, age it, centrifuge it to obtain the precipitate, wash it with methanol by centrifugation, and dry it to obtain ZIF-67 powder; wherein, the aging temperature is 20-25℃ and the aging time is 20-30 hours;
[0022] And / or, the mass-to-volume ratio of Co(NO3)2, methanol, and methanol solution containing 2-methylimidazole is (3-4) g:(40-50) mL:(80-100) mL;
[0023] The mass of 2-methylimidazole in the methanol solution containing 2-methylimidazole is 3.5–4.0 g.
[0024] Secondly, the present invention also provides an F-ZIF-67 / PDMS composite film, which is prepared by the preparation method described above.
[0025] Thirdly, the present invention also provides an application of the aforementioned F-ZIF-67 / PDMS composite film as a negative friction material in the preparation of triboelectric nanogenerators.
[0026] Fourthly, the present invention also provides a triboelectric nanogenerator, comprising a first power generation unit and a second power generation unit;
[0027] The first power generation unit includes a first electrode and a negative friction layer located on the surface of the first electrode;
[0028] The second power generation unit includes a second electrode and a positive friction layer located on the surface of the second electrode;
[0029] The negative friction layer material is the F-ZIF-67 / PDMS composite film.
[0030] The first electrode is electrically connected to the second electrode.
[0031] Preferably, it also includes a first substrate and a second substrate;
[0032] The first substrate is attached to the surface of the first electrode away from the negative friction layer;
[0033] The second substrate is attached to the surface of the second electrode away from the positive friction layer;
[0034] The material of the positive friction layer is PTFE.
[0035] Fifthly, the present invention also provides an application of the aforementioned triboelectric nanogenerator in electrochemical cathodic protection, self-powered sensors, and wearable devices.
[0036] The present invention provides an F-ZIF-67 / PDMS composite thin film, its preparation method and application, and a triboelectric nanogenerator and its application, which have the following advantages over the prior art:
[0037] 1. The preparation method of the F-ZIF-67 / PDMS composite film of the present invention is relatively simple. High-performance F-ZIF-67 / PDMS composite film can be prepared through simple solution mixing, stirring, curing and soaking. This preparation method has the advantages of low cost, simple operation and good repeatability, which is conducive to realizing large-scale production and commercial application.
[0038] 2. ZIF-67, as a metal-organic framework (MOF) material, has abundant pore structure and high specific surface area. Combining it with PDMS can significantly improve the triboelectric properties and charge storage capacity of the film. PDMS itself has good flexibility, biocompatibility and chemical stability. When combined with ZIF-67, it can further enhance the mechanical strength and durability of the material.
[0039] 3. This invention incorporates a metal-organic framework into PDMS, which improves the dielectric constant. Furthermore, the fluorination modification of the ZIF-67 / PDMS film significantly alters the chemical properties of the material surface, particularly increasing its electronegativity and reducing its surface energy. Additionally, the use of PTFE, a material with a significantly different electronegativity, as the positive friction material greatly increases the amount of charge between the friction materials, achieving higher power generation efficiency and more stable output performance. Moreover, TENG can effectively convert mechanical energy into electrical energy, providing a stable and reliable energy supply for low-power electronic devices.
[0040] 4. The triboelectric nanogenerator of the present invention has the advantages of high output efficiency and simple preparation process, which makes the triboelectric nanogenerator of the present invention have broad application prospects and important social significance in the fields of self-powered corrosion prevention, energy harvesting, and environmental monitoring. Attached Figure Description
[0041] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0042] Figure 1 This is a schematic diagram of the structure of the triboelectric nanogenerator of the present invention;
[0043] Figure 2 This is a schematic diagram illustrating the working principle of the triboelectric nanogenerator of the present invention.
[0044] Figure 3 This is a SEM image of the ZIF-67 powder prepared in Example 1 of this invention;
[0045] Figure 4 This is a SEM image of the F-ZIF-67 / PDMS composite film prepared in Example 2 of the present invention;
[0046] Figure 5The XRD patterns of ZIF-67 powder, pure PDMS, F-ZIF-67 / PDMS composite film prepared in Example 2, and ZIF-67 / PDMS composite film prepared in step S3 of Example 2 are shown below.
[0047] Figure 6 The triboelectric output performance of high-performance triboelectric nanogenerators based on pure PDMS, ZIF-67 / PDMS composite films, and F-ZIF-67 / PDMS composite films is shown in the figure.
[0048] Figure 7 This is a rectifier circuit diagram of the triboelectric nanogenerator F-ZIF-67 / PDMS-TENG in Embodiment 3 of the present invention;
[0049] Figure 8 This is a schematic diagram of the self-powered corrosion-resistant system of the triboelectric nanogenerator F-ZIF-67 / PDMS-TENG in Embodiment 3 of the present invention;
[0050] Figure 9 This is a schematic diagram of the OCP curve with and without TENG coupling;
[0051] Figure 10 This is a schematic diagram of the Tafel curve with and without TENG coupling. Detailed Implementation
[0052] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0053] The technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0054] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of embodiments. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a rigid limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single digits within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Additionally, whenever a numerical range is indicated herein, it means including any referenced number (fraction or integer) within the indicated range.
[0055] This application provides a method for preparing an F-ZIF-67 / PDMS composite film, comprising the following steps:
[0056] S1. Add ZIF-67 powder to the PDMS precursor, stir and then ultrasonically disperse to obtain a mixed solution; the PDMS precursor includes a curing agent and a PDMS matrix;
[0057] S2. Vacuum the mixed solution to eliminate air bubbles in the solution;
[0058] S3. Coat the vacuum-sealed mixed solution onto the substrate and cure it to obtain a ZIF-67 / PDMS composite film.
[0059] S4. Immerse the ZIF-67 / PDMS composite film in a fluorosilane solution and dry it to obtain the F-ZIF-67 / PDMS composite film.
[0060] In some embodiments, the fluorosilane solution comprises perfluorodecyltrimethoxysilane and ethanol, wherein the mass concentration of perfluorodecyltrimethoxysilane in the fluorosilane solution is 1-2%.
[0061] In some embodiments, the method for preparing ZIF-67 powder includes the following steps:
[0062] Co(NO3)2 was dissolved in methanol, and then a methanol solution containing 2-methylimidazole was added to obtain a mixture.
[0063] After stirring the mixture, it was aged, centrifuged, and the precipitate was obtained. The precipitate was washed and dried to obtain ZIF-67 powder.
[0064] In some embodiments, the ultrasonic dispersion time is 30–100 min;
[0065] In some embodiments, the mass ratio of curing agent to PDMS matrix is 1:(10-12).
[0066] In some embodiments, the mass ratio of ZIF-67 powder to PDMS precursor is 1:(10-100).
[0067] In some embodiments, the curing time is 1 to 4 hours and the curing temperature is 70 to 90°C.
[0068] In some embodiments, in the step of immersing the ZIF-67 / PDMS composite film in a fluorosilane solution, the immersion temperature is 20-25°C and the time is 2-3 hours.
[0069] In some embodiments, the mixture is stirred for 2-4 hours, aged, centrifuged to obtain a precipitate, washed with methanol by centrifugation, and dried to obtain ZIF-67 powder; wherein the aging temperature is 20-25℃, the aging time is 20-30 hours, the centrifugation speed is 1000-1200 rpm, and the centrifugation time is 1-2 minutes.
[0070] In some embodiments, the mass-to-volume ratio of Co(NO3)2, methanol, and methanol solution containing 2-methylimidazole is (3-4) g:(40-50) mL:(80-100) mL.
[0071] In some embodiments, the mass of 2-methylimidazole in the methanol solution containing 2-methylimidazole is 3.5 to 4.0 g.
[0072] In some embodiments, the substrate is a glass substrate.
[0073] This invention enables the preparation of high-performance F-ZIF-67 / PDMS composite films through simple steps such as solution mixing, stirring, curing, and soaking. This preparation method offers advantages such as low cost, ease of operation, and good reproducibility, facilitating large-scale production and commercial applications. ZIF-67, as a metal-organic framework (MOF) material, possesses abundant pore structure and a high specific surface area; combining it with PDMS significantly enhances the triboelectric properties and charge storage capacity of the film. PDMS itself exhibits good flexibility, biocompatibility, and chemical stability, which, when combined with ZIF-67, can further improve these properties. This invention enhances the mechanical strength and durability of materials by embedding a metal-organic framework into PDMS, thereby increasing the dielectric constant. Furthermore, fluorination modification of the ZIF-67 / PDMS film significantly alters the surface chemical properties, particularly increasing electronegativity and reducing surface energy. The use of PTFE, a material with a significantly different electronegativity, as the positive friction material greatly increases the amount of charge between the friction materials, resulting in higher power generation efficiency and more stable output performance. Additionally, TENG can effectively convert mechanical energy into electrical energy, providing a stable and reliable energy supply for low-power electronic devices.
[0074] Based on the same inventive concept, the present invention also provides an F-ZIF-67 / PDMS composite film, which is prepared by the above-described preparation method.
[0075] Based on the same inventive concept, the present invention also provides an application of the above-mentioned F-ZIF-67 / PDMS composite film as a positive friction material in the preparation of triboelectric nanogenerators.
[0076] Based on the same inventive concept, the present invention also provides a triboelectric nanogenerator, including a first power generation unit and a second power generation unit;
[0077] The first power generation unit includes a first electrode and a negative friction layer located on the surface of the first electrode;
[0078] The second power generation unit includes a second electrode and a positive friction layer located on the surface of the second electrode;
[0079] The negative friction layer material is the aforementioned F-ZIF-67 / PDMS composite film;
[0080] The first electrode is electrically connected to the second electrode.
[0081] The triboelectric nanogenerator of this invention comprises key components such as a positive friction layer, a negative friction layer, electrodes, and wires. The negative friction layer specifically utilizes a hybrid material of fluorinated ZIF-67 and PDMS, namely an F-ZIF-67 / PDMS composite film, while the positive friction layer uses PTFE, a material with a significantly different electronegativity from F-ZIF-67 / PDMS. By introducing ZIF-67 nanoparticles, the dielectric constant of the composite film is significantly improved, and the fluorination modification of the composite film affects the triboelectric polarity of the dielectric layer, thereby enhancing the charge density and output performance of the triboelectric nanogenerator. This triboelectric nanogenerator can efficiently convert mechanical energy in the environment into electrical energy and has been successfully applied to an electrochemical cathodic protection system. This system exhibits excellent corrosion resistance to steels such as Q235 carbon steel, 304SS, and A3 carbon steel, providing a new solution for corrosion protection.
[0082] In some embodiments, a first substrate and a second substrate are also included;
[0083] The first substrate is attached to the surface of the first electrode away from the negative friction layer;
[0084] The second substrate is attached to the surface of the second electrode away from the positive friction layer;
[0085] The material of the positive friction layer is PTFE (polytetrafluoroethylene).
[0086] In some embodiments, an F-ZIF-67 / PDMS composite film is coated on the first electrode as a negative friction material to form a first power generation unit; PTFE is adhered on the second electrode as a positive friction material to form a second power generation unit.
[0087] In some embodiments, the external circuit is connected to the first electrode and the second electrode via wires.
[0088] In some embodiments, the first electrode and the second electrode are materials with good electrical conductivity, such as copper foil, aluminum foil, graphite, etc.; the first substrate and the second substrate are acrylic sheets or any other material with a certain mechanical strength.
[0089] In some embodiments, both the first substrate and the second substrate are 4×4×0.5cm. 3 An acrylic sheet (4cm long, 4cm wide, and 0.5cm high) has a first electrode and a second electrode with a length of 4cm, a width of 4cm, and a thickness of 200μm, and negative and positive friction layers with a length of 4cm, a width of 4cm, and a thickness of 200μm.
[0090] Furthermore, such as Figure 1The diagram shows a schematic of the structure of the triboelectric nanogenerator of the present invention. The triboelectric nanogenerator includes a first power generation unit and a second power generation unit. The first power generation unit includes a first substrate 16, a first electrode 15, and a negative friction layer 14 that are sequentially bonded together. The second power generation unit includes a second substrate 13, a second electrode 12, and a positive friction layer 11. The negative friction layer 14 is an F-ZIF-67 / PDMS composite film, and the positive friction layer 11 is PTFE. A load 17 is connected between the first electrode 15 and the second electrode 12 through a wire.
[0091] For details, please refer to Figure 2 As shown, this illustrates the principle of the triboelectric nanogenerator of the present invention (where both the first and second electrodes are Cu): Initially, neither the negative nor positive friction layers generate electricity before contact. Upon first contact, equal amounts of opposite charges are generated on the surface of the F-ZIF-67 / PDMS composite film and on the PTFE. The F-ZIF-67 / PDMS composite film is negatively charged because it gains electrons more readily than PTFE. When the two electrodes separate, the potential difference between them drives electrons from the first electrode to the second electrode until the potential reaches equilibrium. Under pressure, they move closer together again. Simultaneously, the equilibrium potential is broken again, driving electrons from the second electrode to the first electrode. When they separate and contact, the resulting currents are in opposite directions. Therefore, the triboelectric generator generates periodic alternating currents through repeated separation and contact.
[0092] Based on the same inventive concept, the present invention also provides an application of the above-mentioned triboelectric nanogenerator in electrochemical cathodic protection, self-powered sensors, and wearable devices.
[0093] The triboelectric nanogenerator of the present invention has the advantages of high output efficiency and simple preparation process, which makes it have broad application prospects and important social significance in the fields of self-powered corrosion prevention, energy harvesting, and environmental monitoring.
[0094] The following further illustrates the F-ZIF-67 / PDMS composite film, its preparation method, and its application, as well as the triboelectric nanogenerator and its application, using specific embodiments. This section further illustrates the content of the present invention with reference to specific embodiments, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in the art.
[0095] In the following examples, the PDMS precursor includes a curing agent and a PDMS matrix, specifically Dow Corning SYLGARD 184 silicone rubber, and the curing agent and PDMS matrix are mixed at a mass ratio of 1:10.
[0096] Example 1
[0097] This application provides a method for preparing ZIF-67 powder, including the following steps:
[0098] S1, 3.3g of Co(NO3)2·6H2O was dissolved in 45mL of methanol, and then 90mL of methanol solution containing 3.7g of 2-methylimidazole was added and mixed to obtain a mixture.
[0099] S2. After magnetically stirring the mixture in S1 for 2 hours, place it in an aging chamber and age it at room temperature (25℃) for 24 hours. The resulting purple precipitate is washed 6 times by centrifugation with methanol and dried overnight in a vacuum oven at 60℃ to obtain ZIF-67 powder.
[0100] Figure 3 Here is a SEM image of the ZIF-67 powder prepared in Example 1; from Figure 3 As can be seen, ZIF-67 powder exhibits many smooth, randomly oriented polyhedral or rhombic dodecahedral morphologies. The synthesized ZIF-67 particles range in size from 400 nm to 500 nm, with a small amount of agglomeration.
[0101] Example 2
[0102] This embodiment provides a method for preparing an F-ZIF-67 / PDMS composite film, including the following steps:
[0103] S1. Add ZIF-67 powder to the PDMS precursor, stir and then ultrasonically disperse for 30 min to obtain a mixed solution; the PDMS precursor includes a curing agent and a PDMS matrix; the mass ratio of the curing agent to the PDMS matrix is 1:10; the mass fraction of ZIF-67 powder in the mixed solution is 5 wt%; the preparation method of ZIF-67 powder is the same as in Example 1;
[0104] S2. Vacuum the mixed solution to eliminate air bubbles in the solution;
[0105] S3. The vacuum-sealed mixed solution is coated onto the glass substrate using a doctor blade and then transferred to an 80°C oven for curing for 2 hours to form a 200μm thick ZIF-67 / PDMS composite film on the surface of the glass substrate.
[0106] S4. The ZIF-67 / PDMS composite film was immersed in a fluorosilane solution at room temperature (25℃) for 2 hours and then dried to obtain the F-ZIF-67 / PDMS composite film. The fluorosilane solution included perfluorodecyltrimethoxysilane and ethanol, and the mass concentration of perfluorodecyltrimethoxysilane in the fluorosilane solution was 1 wt%.
[0107] Figure 4 The image shows a SEM image of the F-ZIF-67 / PDMS composite film prepared in Example 2.
[0108] from Figure 4 As can be seen, ZIF-67 nanoparticles can be uniformly distributed in PDMS and adhere tightly to PDMS, thus ensuring the high performance and durability of the device.
[0109] Figure 5 The XRD patterns are those of ZIF-67 powder, pure PDMS (i.e., pure PDMS obtained by mixing curing agent and PDMS matrix at a mass ratio of 1:10 and then curing), F-ZIF-67 / PDMS composite film prepared in Example 2, and ZIF-67 / PDMS composite film prepared in step S3 of Example 2.
[0110] from Figure 5 As can be seen, compared with ZIF-67 alone and ZIF-67 / PDMS, the addition of ZIF-67 disrupts the crystal structure of PDMS. In addition, ZIF-67 / PDMS has obvious diffraction peaks at 2θ = 7.31°, 12.72°, 18.04°, 26.7°, 29.67° and 31.55° corresponding to the crystal plane of ZIF-67, which indicates that the bonding is successful. However, for the F-ZIF-67 / PDMS composite film, its XRD pattern is similar to that of the ZIF-67 / PDMS composite film, and no significant changes in crystal structure were observed, indicating that the fluorosilane treatment process did not change the overall crystal morphology of the composite material. Nevertheless, since the immersion treatment of the sample in the fluorosilane solution may have caused some ZIF-67 powder to fall off or its content to decrease, the intensity of the characteristic diffraction peak of ZIF-67 in the corresponding XRD pattern was relatively weakened. This observation further supports the potential influence of fluorosilane treatment on the ZIF-67 content in the ZIF-67 / PDMS composite material.
[0111] Example 3
[0112] This embodiment provides a triboelectric nanogenerator, including a first power generation unit and a second power generation unit;
[0113] The first power generation unit includes a first electrode and a negative friction layer located on the surface of the first electrode;
[0114] The second power generation unit includes a second electrode and a positive friction layer located on the surface of the second electrode;
[0115] The negative friction layer material is the F-ZIF-67 / PDMS composite film prepared in Example 2;
[0116] The first electrode is electrically connected to the second electrode;
[0117] It also includes a first substrate and a second substrate;
[0118] The first substrate is attached to the surface of the first electrode away from the negative friction layer;
[0119] The second substrate is attached to the surface of the second electrode away from the positive friction layer;
[0120] The material of the positive friction layer is PTFE (polytetrafluoroethylene);
[0121] Both the first electrode and the second electrode are copper foils;
[0122] Both the first and second bases are 4×4×0.5cm. 3 An acrylic sheet (4cm long, 4cm wide, and 0.5cm high) has a first electrode and a second electrode with a length of 4cm, a width of 4cm, and a thickness of 200μm, and negative and positive friction layers with a length of 4cm, a width of 4cm, and a thickness of 200μm.
[0123] Comparative Example 1
[0124] The triboelectric nanogenerator provided in this comparative example is the same as that in Example 3, except that the negative friction layer material is the ZIF-67 / PDMS composite film prepared in step S3 of Example 2, and the rest is the same as that in Example 3.
[0125] Comparative Example 2
[0126] The triboelectric nanogenerator provided in this comparative example is the same as that in Example 3, except that the negative friction layer material is pure PDMS (i.e., the curing agent and PDMS matrix are mixed at a mass ratio of 1:10 and then cured to obtain pure PDMS). All other aspects are the same as those in Example 3.
[0127] Figure 6 The triboelectric output performance of high-performance triboelectric nanogenerators based on pure PDMS, ZIF-67 / PDMS composite films, and F-ZIF-67 / PDMS composite films, prepared according to the methods in Comparative Examples 1-2 and Example 3, was evaluated. Specifically, Figure 6PDMS-PTFE represents a triboelectric nanogenerator based on pure PDMS, ZIF-67 / PDMS-PTFE represents a triboelectric nanogenerator based on ZIF-67 / PDMS composite film, and F-ZIF-67 / PDMS-PTFE represents a triboelectric nanogenerator based on F-ZIF-67 / PDMS composite film.
[0128] Under the action of an external force at a frequency of 3 Hz, the positive and negative friction layers achieved contact and separation. With the addition of ZIF-67, the output performance of the TENG was improved significantly. The TENG reached its highest output performance after fluorination modification of ZIF-67 / PDMS, with voltage, current, and charge reaching a maximum of 187.14 V, 37.46 μA, and 72.54 nC, respectively, fully demonstrating the high-performance output characteristics of this TENG. Therefore, the addition of ZIF-67 powder effectively improved the output performance of the TENG. This is mainly because the addition of ZIF-67 particles increases the surface roughness of the PDMS composite film. This increased roughness helps to generate more effective contact area during friction, thereby increasing charge transfer and accumulation, and improving the output performance of the TENG. In addition, fluorination modification enhances the frictional effect with PTFE by changing the microstructure or chemical properties of the PDMS surface. This enhancement is due to the increased surface roughness of PDMS after fluorination, or the enhanced interaction between fluorine atoms and fluorine atoms in PTFE.
[0129] Figure 7 The high-performance triboelectric nanogenerator F-ZIF-67 / PDMS-TENG in Example 3 is connected to a rectifier bridge, which converts the alternating current (AC) generated by F-ZIF-67 / PDMS-TENG into direct current (DC). The DC power is then fed into external electronic components, easily lighting up 111 LEDs.
[0130] Due to its excellent output performance, the high-performance triboelectric nanogenerator F-ZIF-67 / PDMS-TENG in Example 3 was used as the cathodic protection power source to construct a self-powered corrosion protection system. Figure 8A self-powered corrosion-resistant system based on F-ZIF-67 / PDMS-TENG is demonstrated. Specifically, the F-ZIF-67 / PDMS-TENG is connected to a rectifier bridge. The working electrode is made of Q235 carbon steel (connected to the negative electrode of the rectifier bridge), and the counter electrode is a platinum electrode (connected to the positive electrode of the rectifier bridge). Both the Q235 carbon steel and platinum electrodes are placed in a 3.5 wt% NaCl solution. The F-ZIF-67 / PDMS-TENG injects electrons into the carbon steel surface through the rectifier circuit, causing cathode polarization and preventing metal corrosion. In a three-electrode system (working electrode is Q235 carbon steel, counter electrode is platinum electrode, reference electrode is saturated calomel electrode (SCE), electrolyte is 3.5% NaCl aqueous solution), the OCP change of Q235 carbon steel with and without TENG alternating coupling was measured. Figure 9 As shown, the potential of carbon steel remained at -1.02V vs. SCE. When TENG was added to the system, the OCP value of carbon steel shifted sharply to -1.3V vs. SCE. When TENG was removed, the OCP returned to its original value. In the metal corrosion test, the greater the decrease in OCP, the better the corrosion resistance. The Tafel curve of carbon steel was also measured, and the results are shown below. Figure 10 As shown, its potential is more negative than without TENG protection, with a potential reduction of approximately 150mV. This finding further demonstrates the effectiveness of the self-powered corrosion protection system and echoes the OCP reduction observed in previous tests. Furthermore, the self-powered corrosion protection system composed of F-ZIF-67 / PDMS-TENG effectively prevents metal corrosion.
[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An application of a triboelectric nanogenerator in electrochemical cathodic protection; The triboelectric nanogenerator includes a first power generation unit and a second power generation unit; The first power generation unit includes a first electrode and a negative friction layer located on the surface of the first electrode; The second power generation unit includes a second electrode and a positive friction layer located on the surface of the second electrode; in, The negative friction layer material is an F-ZIF-67 / PDMS composite film; The first electrode is electrically connected to the second electrode; The preparation method of the F-ZIF-67 / PDMS composite film includes the following steps: ZIF-67 powder was added to the PDMS precursor, stirred, and then ultrasonically dispersed to obtain a mixed solution; the PDMS precursor includes a curing agent and a PDMS matrix; Vacuum the mixed solution to eliminate air bubbles in the solution; The vacuum-sealed mixed solution was coated onto the substrate and cured to obtain a ZIF-67 / PDMS composite film. The ZIF-67 / PDMS composite film was immersed in a fluorosilane solution and dried to obtain the F-ZIF-67 / PDMS composite film. The fluorosilane solution is composed of perfluorodecyltrimethoxysilane and ethanol, wherein the mass fraction of perfluorodecyltrimethoxysilane in the fluorosilane solution is 1 wt%. The method for preparing the ZIF-67 powder includes the following steps: Co(NO3)2 was dissolved in methanol, and then a methanol solution containing 2-methylimidazole was added to obtain a mixture. After stirring the mixture, it was aged, centrifuged to obtain a precipitate, washed, and dried to obtain ZIF-67 powder; In the step of immersing the ZIF-67 / PDMS composite film in a fluorosilane solution, the immersion temperature is 20~25℃ and the time is 2~3h; The mass ratio of the curing agent to the PDMS matrix is 1:(10~12); The mass fraction of ZIF-67 powder in the mixed solution is 5 wt%. The mass-to-volume ratio of Co(NO3)2, methanol, and methanol solution containing 2-methylimidazole is (3~4) g:(40~50) mL:(80~100) mL. The mass of 2-methylimidazole in the methanol solution containing 2-methylimidazole is 3.5~4.0 g; The material of the positive friction layer is PTFE.
2. The application as described in claim 1, characterized in that, The ultrasonic dispersion time is 30~100 min; And / or, the curing time is 1~4h, and the curing temperature is 70~90℃.
3. The application as described in claim 1, characterized in that, After stirring the mixture for 2-4 hours, it was aged, centrifuged, and the precipitate was obtained. The precipitate was washed with methanol by centrifugation and dried to obtain ZIF-67 powder. The aging temperature was 20-25℃ and the aging time was 20-30 hours.
4. The application as described in claim 1, characterized in that, The triboelectric nanogenerator also includes a first substrate and a second substrate; The first substrate is attached to the surface of the first electrode away from the negative friction layer; The second substrate is attached to the surface of the second electrode away from the positive friction layer.
Citation Information
Patent Citations
Personal energy managing device containing fluoroalkyl silane hydrophobic surface layer and production and application of personal energy managing device
CN105603725A
Friction nano-generator
CN111200376A
Nano-composite membrane based on fibroin and zeolite imidazole framework material as well as preparation method and application of nano-composite membrane
CN116904037A
